Hediste Malmgren 1867 - Salazar-Vallejo, Sergio I.; León-González, Jesús Angel De; Conde-Vela, Víctor M. (Zenodo, 2021)
Key to species of Hediste Malmgren, 1867 1. Areas VII–VIII with a single row of denticles (rarely 2–5 supernumerary paragnaths)...............2 – Areas VII–VIII with two rows of denticles; palpophores continuous, 3–4 × as long as wide; area II with about 15 paragnaths per side...............................................................................................7 2. Palpophores with a transverse depression (looking bisegmented); longest tentacular cirri reaching chaetigers 2–3; area II with about 15 medium-sized paragnaths per side................................................................................................................................ H. limnicola (Johnson, 1903) (California) – Palpophores continuous, 2 × as long as wide...................................................................................3 3. Area II with 10 or fewer large paragnaths per side; longest tentacular cirri reaching chaetigers 6–9; areas VII–VIII with 19–26 paragnaths.............................. H. japonica (Izuka, 1908) (Japan) – Area II with more than 20 tiny paragnaths per side; longest tentacular cirri reaching chaetigers 8–9; areas VII–VIII with 9–35 paragnaths............... H. atoka Sato & Nakashima, 2003 (Japan) – Area II with 10–20 paragnaths........................................................................................................4 4. Areas VII–VIII with 8 paragnaths; longest tentacular cirri reaching chaetiger 5................................................................................. H. sakhalinensis (Okuda, 1935) (Sakhalin Island, Japan Sea) – Areas VII–VIII with 11–41 paragnaths..........................................................................................5 5. Posterior parapodia with median ligule as long as dorsal one; longest tentacular cirri reaching chaetigers 6–12...................................................... H. diadroma Sato & Nakashima, 2003 (Japan) – Posterior parapodia with median ligule markedly smaller than dorsal one.................................6 6. Longest tentacular cirri reaching chaetiger 6.................. H. lighti (Hartman, 1938) (California) – Longest tentacular cirri reaching chaetiger 2...... H. rabatensis (Mohammad, 1989) (Morocco) 7. Neuropodial anchylosed falcigers subdistally constricted; tentacular cirri reaching chaetigers 5–7.................................... H. diversicolor (Müller, 1776) sensu Hartmann-Schröder 1996 (Baltic Sea) – Neuropodial anchylosed falcigers subdistally swollen; tentacular cirri reaching chaetigers 5–9.......................................................................................................................................... H. diversicolor (Müller, 1776) sensu Khlebovich 1996 (Black Sea; matching N. falsa (de Quatrefages, 1866)) Remarks Smith (1959), after comparing the types, concluded that H. lighti was a junior synonym of H. limnicola . They differ in pigmentation in living specimens, H. limnicola being reddish, whereas H. lighti is transparent. A more detailed comparison is needed to confirm this synonymy. Day (1967) described Nereis gilchristi based on a single small specimen (8 mm long, 40 chaetigers) collected in South Africa. He indicated that it has only two notopodial ligules in anterior chaetigers, which is an important difference and deserves a separate assessment when assigning it to a genus. The key above should be used cautiously because the status of the type species must be clarified, since there are two cryptic species in the Baltic Sea (Röhner et al . 1997; Virgilio et al. 2006; Audzijonyte et al . 2008), and some Mediterranean and Black Sea forms (Virgilio et al . 2009; Cossu et al . 2012) might necessitate the reestablishment of some names currently regarded as junior synonyms. : Published as part of Salazar-Vallejo, Sergio I., León-González, Jesús Angel De & Conde-Vela, Víctor M., 2021, Revision of the species confused with " Nereis falsa " de Quatrefages, 1866 (Annelida, Nereididae), pp. 1-70 in European Journal of Taxonomy 779 on pages 9-10, DOI: 10.5852/ejt.2021.779.1579, http://zenodo.org/record/5724311 : {"references": ["Malmgren A. J. 1867. Annulata Polychaeta Spetsbergiae, Groenlandiae, Islandiae et Scandinaviae hactenus cognita. Frenckelliana, Helsingsforsiae [Helsinki]. https: // doi. org / 10.5962 / bhl. title. 13358", "Hartman O. 1938. Annotated list of the types of polychaetous annelids in the Museum of Comparative Zoology. Bulletin of the Museum of Comparative Zoology at Harvard College 85: 1 - 31.", "Muller O. F. 1776. Zoologiae Danicae Prodromus, seu Animalium Daniae et Norvegiae Indigenarum Characters, Nomina, et Synonyma Imprimis Popularium. Hallageriis, Havniae [Copenhagen]. https: // doi. org / 10.5962 / bhl. title. 13268", "Hartmann-Schroder G. 1996. Annelida, Borstenwurmer, Polychaeta. Tierwelt Deutschlands 58: 1 - 648.", "Khlebovich V. V. 1996. Polychaetous annelids 3. Polychaetes of the family Nereididae of the Russian seas and adjacent waters. Fauna of Russia and Neighbouring Countries, Zoological Institute, Russian Academy of Sciences, New Series 140: 1 - 223. [In Russian.]", "Smith R. I. 1959. The synonymy of the viviparous polychaete Neanthes lighti Hartman (1938) with Nereis limnicola Johnson (1903). Pacific Science 13: 349 - 350.", "Day J. H. 1967. A monograph on the Polychaeta of Southern Africa. British Museum (Natural History) Publication 656, 2 volumes. https: // doi. org / 10.5962 / bhl. title. 8596", "Rohner M., Bastrop R. & Jurss K. 1997. Genetic differentiation in Hediste diversicolor (Polychaeta: Nereididae) for the North Sea and the Baltic Sea. Marine Biology 130: 171 - 180. https: // doi. org / 10.1007 / s 002270050236", "Virgilio M., Backeljau T. & Abbiati M. 2006. Mitochondrial DNA and allozyme patterns of Hediste diversicolor (Polychaeta: Nereididae): the importance of small scale genetic structuring. Marine Ecology Progress Series 326: 157 - 165. https: // doi. org / 10.3354 / meps 326157", "Audzijonyte A., Ovcarenko I., Bastrop R. & Vainola R. 2008. Two cryptic species of the Hediste diversicolor group (Polychaeta, Nereididae) in the Baltic Sea, with mitochondrial signatures of different population histories. Marine Biology 155: 599 - 612. https: // doi. org / 10.1007 / s 00227 - 008 - 1055 - 3", "Virgilio M., Fauvelot C., Constantini F., Abbiati M. & Backeljau T. 2009. Phylogeography of the common ragworm Hediste diversicolor (Polychaeta: Nereididae) reveals cryptic diversity and multiple colonization events across its distribution. Molecular Ecology 18: 1980 - 1994. https: // doi. org / 10.1111 / j. 1365 - 294 X. 2009.04170. x", "Cossu P., Maltagliati F., Lai T., Casu M., Curini-Galletti & Castelli A. 2012. Genetic structure of Hediste diversicolor (Polychaeta, Nereididae) from the northwestern Mediterranean as revealed by DNA intersimple sequence repeat (ISSR) markers. Marine Ecology Progress Series 452: 171 - 178. https: // doi. org / 10.3354 / meps 09611"]}